2011
DOI: 10.1534/genetics.110.125369
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Component of the Disulfide-Reducing Pathway Required for Cytochrome c Assembly in Plastids

Abstract: In plastids, the conversion of energy in the form of light to ATP requires key electron shuttles, the c-type cytochromes, which are defined by the covalent attachment of heme to a CXXCH motif. Plastid c-type cytochrome biogenesis occurs in the thylakoid lumen and requires a system for transmembrane transfer of reductants. Previously, CCDA and CCS5/HCF164, found in all plastid-containing organisms, have been proposed as two components of the disulfide-reducing pathway. In this work, we identify a small novel pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
42
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(43 citation statements)
references
References 63 publications
1
42
0
Order By: Relevance
“…LPA1 homologues are present in Ostreococcus and in Chlamydomonas, in which REP27 (repair-aberrant mutant of PSII) is the LPA1 homologue. In contrast to the inactivation of LPA1, inactivation of REP27 [57] does not affect the accumulation of PSII subunits other than the D1 protein [18]. REP27 is specifically required for efficient D1 turnover but is not essential for de novo biogenesis and assembly of PSII [18].…”
Section: Regulatory Factors For Psii Assemblymentioning
confidence: 87%
“…LPA1 homologues are present in Ostreococcus and in Chlamydomonas, in which REP27 (repair-aberrant mutant of PSII) is the LPA1 homologue. In contrast to the inactivation of LPA1, inactivation of REP27 [57] does not affect the accumulation of PSII subunits other than the D1 protein [18]. REP27 is specifically required for efficient D1 turnover but is not essential for de novo biogenesis and assembly of PSII [18].…”
Section: Regulatory Factors For Psii Assemblymentioning
confidence: 87%
“…These proteins define a trans-thylakoid pathway for the delivery of reductants from stroma to lumen (Lennartz et al, 2001;Page et al, 2004;Hisabori, 2006, 2010;Gabilly et al, 2010Gabilly et al, , 2011. Operation of the trans-thylakoid pathway is needed to reduce disulfides in target proteins, a process essential for photosynthesis (Lennartz et al, 2001;Page et al, 2004;Gabilly et al, 2010Gabilly et al, , 2011.…”
Section: Introductionmentioning
confidence: 99%
“…Operation of the trans-thylakoid pathway is needed to reduce disulfides in target proteins, a process essential for photosynthesis (Lennartz et al, 2001;Page et al, 2004;Gabilly et al, 2010Gabilly et al, , 2011.…”
Section: Introductionmentioning
confidence: 99%
“…It is suggested that electrons provided by stromal thioredoxin are transferred to the lumen via CCDA and HCF164/CCS5 to the oxidized CxxCH motif of the apocytochrome f, thereby generating the necessary sulfhydryls for heme ligation (Motohashi and Hisabori, 2006). Recently, the protein CCS4 was identified in Chlamydomonas reinhardtii that also is an essential component for heme attachment to cytochrome f (and cytochrome c 6 ); its exact role is yet unclear, but there is evidence that it is involved in the disulfidereducing pathway at the thylakoids (Gabilly et al, 2011). While heme binding in the lumen absolutely requires the transthylakoid disulfide-reducing pathway, covalent attachment of heme c n to Cys-35 of cytochrome b 6 requires the CCB (for cofactor-binding, Cytb6f complex, and cytochrome b 6 ) factors 1 to 4 at the stromal site of the membrane (Saint-Marcoux et al, 2009).…”
mentioning
confidence: 99%